Exploring host-guest complexation mechanisms by a molecular dynamics/quantum mechanics/continuum solvent model approach - Ye, Renlong; Nie, Xuemei; Zhou, Yumei; Wong, Chung F.; Gong, Xuedong; Jiang, Wei; Tang, Weihua; Wang, Yan A.; Heine, Thomas; Zhou, Baojing (Chemical Physics Letters, 2016)
We introduce a molecular dynamics/quantum mechanics/continuum solvent model (MD/QM/CSM) approach to investigate binding mechanisms of host-guest systems. The representative conformations of host, guest, and their complex generated from MD simulations at the molecular-mechanics level are used for binding free energy calculations based on a QM/CSM model. We use this approach to explore the binding mechanisms of β-cyclodextrin (β-CD) and 2, 6-di-methyl-β-CD (DM-β-CD) with various guest molecules. Our results suggest that solvent effects play a more important role in determining the relative binding affinities of DM-β-CD than those of β-CD mainly because the former is more flexible than the latter.
CRIS-Team Scopus Importer:2023-03-20